2020
DOI: 10.1213/ane.0000000000003975
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intrathecal Fentanyl for Cesarean Delivery: A Systematic Review and Meta-analysis of Randomized Controlled Trials With Trial Sequential Analysis

Abstract: BACKGROUND: Fentanyl and morphine are the 2 most commonly added opioids to bupivacaine for spinal anesthesia during cesarean delivery. Numerous clinical trials have assessed efficacy and safety of different doses of fentanyl added to intrathecal bupivacaine for spinal anesthesia, yet its benefit, harm, and optimal dose remain unclear. This study aimed to systematically review the evidence of the efficacy of fentanyl when added to intrathecal bupivacaine alone and when added to bupivacaine with morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Opioids are still currently being used as adjuvants to intrathecal blocks as side effects are minimal, and they can be safely used in the elderly as well as pregnant patients and ease of availability makes them a practical choice. [ 17 18 19 20 21 22 23 24 25 26 27 ] Previous systematic reviews have evaluated the safety and efficacy of intrathecal opioids (Fentanyl) as adjuvants for spinal anesthesia. [ 17 18 19 ] A study conducted by Wang and et al on the effects of intrathecal bupivacaine and bupivacaine plus fentanyl in elderly patients undergoing total hip arthroplasty showed that although the quality of anesthesia was the same, the fentanyl group showed less use of ephedrine for stable hemodynamics and a longer duration for postoperative analgesic use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioids are still currently being used as adjuvants to intrathecal blocks as side effects are minimal, and they can be safely used in the elderly as well as pregnant patients and ease of availability makes them a practical choice. [ 17 18 19 20 21 22 23 24 25 26 27 ] Previous systematic reviews have evaluated the safety and efficacy of intrathecal opioids (Fentanyl) as adjuvants for spinal anesthesia. [ 17 18 19 ] A study conducted by Wang and et al on the effects of intrathecal bupivacaine and bupivacaine plus fentanyl in elderly patients undergoing total hip arthroplasty showed that although the quality of anesthesia was the same, the fentanyl group showed less use of ephedrine for stable hemodynamics and a longer duration for postoperative analgesic use.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 18 19 20 21 22 23 24 25 26 27 ] Previous systematic reviews have evaluated the safety and efficacy of intrathecal opioids (Fentanyl) as adjuvants for spinal anesthesia. [ 17 18 19 ] A study conducted by Wang and et al on the effects of intrathecal bupivacaine and bupivacaine plus fentanyl in elderly patients undergoing total hip arthroplasty showed that although the quality of anesthesia was the same, the fentanyl group showed less use of ephedrine for stable hemodynamics and a longer duration for postoperative analgesic use. [ 19 ] Ravindran et al studied two doses of intrathecal buprenorphine as an adjuvant to 0.5% hyperbaric bupivacaine for cesarean sections and concluded that the addition of 60 mcg provided longer duration of postoperative analgesia as compared to 45 mcg and reported no side effects on mother as well as fetus.…”
Section: Discussionmentioning
confidence: 99%
“…2 A 2020 meta-analysis that included 14 randomized controlled trials with 694 patients undergoing cesarean delivery with spinal anesthesia showed that 17 of 370 patients (4.6%) who received intrathecal fentanyl with bupivacaine required systemic anesthetic adjunct medication compared to 96 of 324 (29.6%) patients who received only bupivacaine, a result that was statistically significant (P<0.001). 5 Increased pain is a potential consequence of using lower doses of intrathecal bupivacaine for cesarean deliveries performed with spinal anesthesia. A 2011 meta-analysis showed a higher risk for systemic anesthetic adjunct supplementation in patients who received <8 mg of subarachnoid bupivacaine for cesarean delivery with spinal anesthesia compared to patients who received >8 mg. 6 Studies published in 2004 and 2017 showed the ED95 (effective) dose of hyperbaric bupivacaine for cesarean delivery to be 11.2 mg and 12.6 mg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…reduce the incidence of IONV. [7] Particularly, intrathecal fentanyl has been reported to effectively improve the quality of regional anesthesia. [1,[8][9][10][11][12][13] However, opioid use causes several complications including pruritus [7][8][9][10]12] , and accidental opioid overdose.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Particularly, intrathecal fentanyl has been reported to effectively improve the quality of regional anesthesia. [1,[8][9][10][11][12][13] However, opioid use causes several complications including pruritus [7][8][9][10]12] , and accidental opioid overdose. [14][15][16][17] In addition, intrathecal fentanyl was reported to cause acute opioid tolerance.…”
Section: Introductionmentioning
confidence: 99%